Effects of an anti-inflammatory VAP-1/SSAO inhibitor, PXS-4728A, on pulmonary neutrophil migration. Issue 1 (December 2015) - Schilter, Heidi; Collison, Adam; Russo, Remo; Foot, Jonathan; Yow, Tin; Vieira, Angelica; Tavares, Livia; Mattes, Joerg; Teixeira, Mauro; Jarolimek, Wolfgang
Abstract Background and purpose The persistent influx of neutrophils into the lung and subsequent tissue damage are characteristics of COPD, cystic fibrosis and acute lung inflammation. VAP-1/SSAO is an endothelial bound adhesion molecule with amine oxidase activity that is reported to be involved in neutrophil egress from the microvasculature during inflammation. This study explored the role of VAP-1/SSAO in neutrophilic lung mediated diseases and examined the therapeutic potential of the selective inhibitor PXS-4728A. Methods Mice treated with PXS-4728A underwent intra-vital microscopy visualization of the cremaster muscle upon CXCL1/KC stimulation. LPS inflammation, Klebsiella pneumoniae infection, cecal ligation and puncture as well as rhinovirus exacerbated asthma models were also assessed using PXS-4728A. Results Selective VAP-1/SSAO inhibition by PXS-4728A diminished leukocyte rolling and adherence induced by CXCL1/KC. Inhibition of VAP-1/SSAO also dampened the migration of neutrophils to the lungs in response to LPS, Klebsiella pneumoniae lung infection and CLP induced sepsis; whilst still allowing for normal neutrophil defense function, resulting in increased survival. The functional effects of this inhibition were demonstrated in the RV exacerbated asthma model, with a reduction in cellular infiltrate correlating with a reduction in airways hyperractivity. Conclusions and implications This study demonstrates that the endothelial cell ligand VAP-1/SSAO contributes to the migration of neutrophils during acute lung inflammation, pulmonary infection and airway hyperractivity. These results highlight the potential of inhibiting of VAP-1/SSAO enzymatic function, by PXS-4728A, as a novel therapeutic approach in lung diseases that are characterized by neutrophilic pattern of inflammation.